2013
DOI: 10.2106/jbjs.l.01705
|View full text |Cite
|
Sign up to set email alerts
|

Societal and Economic Impact of Anterior Cruciate Ligament Tears

Abstract: ACL reconstruction is the preferred cost-effective treatment strategy for ACL tears and yields reduced societal costs relative to rehabilitation once indirect cost factors, such as work status and earnings, are considered. The cost of an ACL tear over the lifetime of a patient is substantial, and resources should be directed to developing innovations for injury prevention and for altering the natural history of an ACL injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
257
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 386 publications
(266 citation statements)
references
References 16 publications
3
257
1
5
Order By: Relevance
“…Lastly, as a group, orthopedic surgeons will be wise to justify reimbursement by proving the value of their work. The AAOS is already leading this effort by demonstrating the cost-effectiveness of several common orthopedic interventions [80][81][82][83].…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, as a group, orthopedic surgeons will be wise to justify reimbursement by proving the value of their work. The AAOS is already leading this effort by demonstrating the cost-effectiveness of several common orthopedic interventions [80][81][82][83].…”
Section: Resultsmentioning
confidence: 99%
“…They showed that the incidence of meniscal tear was higher in the late reconstruction group (71.2 % versus 41.7%). They recommended early surgery to prevent meniscal injury 16 . This study was not a randomised study comparing early with late reconstruction and the numbers in each subgroup were small for statistical comparison.…”
Section: Secondary Meniscus Injurymentioning
confidence: 99%
“…Dr. Schafer: This study is part of a series of papers on the value of treatment for select musculoskeletal conditions supported by AAOS. Studies recently were published on total knee replacement [6], ACL reconstruction [5], and the repair of full thickness rotator cuff tears [4]. This important research on the economic and social value of orthopedic care will continue to gain recognition as additional specific treatment examples are published.…”
Section: Dr Leopoldmentioning
confidence: 99%